The Mechanism of Acupuncture in Treating Essential Hypertension: A Narrative Review - Juan Li; Mingsheng Sun; Jing Ye; Yuxi Li; Rongjiang Jin; Hui Zheng; Fanrong Liang (International Journal of Hypertension)
Essential hypertension has a high incidence worldwide, and patients with essential hypertension endure a lifetime of medication, leading to a heavy economic burden on the patient’s family and causing serious impacts on the patient’s quality of life. Much evidence has demonstrated that acupuncture as an adjunctive therapy can lower blood pressure in patients with hypertension, but the mechanism of its action is unclear. This article reviews the research from 2000 to 2018 regarding the mechanism of acupuncture for hypertension, and we summarize the current knowledge about using acupuncture for hypertension. We found that the mechanism whereby acupuncture lowers blood pressure is related to the regulation of renin-angiotensin-aldosterone system, vascular endothelium, oxidative stress, neuroendocrine system, and so on. Besides, there may be cross-talk between multiple systems and multiple targets. We also investigate the influence factors of acupuncture for hypertension. These results may provide evidence and research ideas for the treatment of hypertension via acupuncture.